2010
DOI: 10.1200/jco.2009.24.7643
|View full text |Cite
|
Sign up to set email alerts
|

Intense Dose-Dense Sequential Chemotherapy With Epirubicin, Paclitaxel, and Cyclophosphamide Compared With Conventionally Scheduled Chemotherapy in High-Risk Primary Breast Cancer: Mature Results of an AGO Phase III Study

Abstract: IDD-ETC was less well tolerated compared with conventional chemotherapy but significantly improved event-free and overall survivals in patients with high-risk primary breast cancer who had four or more positive axillary lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 22 publications
6
111
1
8
Order By: Relevance
“…The significance of dose intensity was also confirmed with the 'intense dose-dense' regimen comprising epirubicin, paclitaxel and cyclophosphamide every 2 weeks. This regimen proved more effective compared to the standard regimen of epirubicin̸cyclophosphamide and improved event-free and overall survival; however, it was also more toxic, leading to four cases (0.6% of the patients) with therapy-related AML̸MDS (30). Therefore, the increased risk of secondary leukemia must be considered when assessing the potential benefits of higher compared to standard doses.…”
Section: Risks Following Chemotherapy Leukemia and Mds Patt Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of dose intensity was also confirmed with the 'intense dose-dense' regimen comprising epirubicin, paclitaxel and cyclophosphamide every 2 weeks. This regimen proved more effective compared to the standard regimen of epirubicin̸cyclophosphamide and improved event-free and overall survival; however, it was also more toxic, leading to four cases (0.6% of the patients) with therapy-related AML̸MDS (30). Therefore, the increased risk of secondary leukemia must be considered when assessing the potential benefits of higher compared to standard doses.…”
Section: Risks Following Chemotherapy Leukemia and Mds Patt Et Almentioning
confidence: 99%
“…That study reported a 5-year incidence of AML of 0.3-1.2%, with an increased risk for greater dose intensity. However, at least two reports from the clinical trial series indicated that the risk of leukemia may rise sharply with more intensive, higher-dose chemotherapy regimens (28)(29)(30), indicating that these patients must be closely monitored for the late effects of therapy. In addition, patients treated with standard cumulative doses of adjuvant epirubicin (≤720 mg̸m 2 ) and cyclophosphamide (≤6,300 mg̸m 2 ) for early BC have a lower probability of secondary leukemia compared to patients treated with higher cumulative doses (29).…”
Section: Risks Following Chemotherapy Leukemia and Mds Patt Et Almentioning
confidence: 99%
“…The IDD-ETC regimen is highly effective and safe (19) but has a pronounced hematological toxicity. Our study did not evaluate treatment of chemotherapy-induced anemia as much as prevention of this anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Pacientes com acometimento de linfonodos são consideradas como um subgrupo de prognóstico desfavorável, ou seja, com uma maior probabilidade de desenvolver metástase em órgãos distantes (MOEBUS et al, 2010). A busca por marcadores moleculares como fatores preditivos do acometimento de linfonodos em câncer de mama auxilia na seleção mais precisa das pacientes nas quais a dissecação dos linfonodos axilares é indicada em relação às pacientes em que esse procedimento é desnecessário (CHENG et al, 2011).…”
Section: Introductionunclassified